QUANTITATIVE ANALYSIS OF THE IMPACTS OF THE PROCESS OF ACCULTURATION ON MERGER OF THE COMPANIES Y AND Z - Santos, Guilherme Carneiro Felippe dos; Tomei, Patricia Amelia (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
This study has the purpose of examine the effects of the cultural integration process between the merger of companies Y and Z, based on a quantitative analysis. The data collection instrument used in the research consisted of a questionnaire based on the conceptual research model developed by Liao and Yen (2003), composed of questions relating to organizational culture and employee work attitudes, based in a Llikert scale. The survey response rate was 67% and is composed of 16 respondents originating from company Y and 14 respondents originating from company Z. Data analysis was made through a non-parametric statistical test, Mann-Whitney (U-test), due to the violation of the requirements for normal application of the t-test. The statistical results of the research point to the existence of different cultural perceptions among the members from each previous company, thereby implying that the merger integration process is still incomplete.